Effects of production and fruit thinning on the off-season production of 'Murcott' tangor - Sales Marinho, Cláudia; de Souza, Maurício (Pesquisa Agropecuaria Brasileira, 1997)
This work aimed to verify the effects of production intensity of 'Murcott' tangor fruits in the past harvest and of the production year thinning in the off-season production. This experiment was conducted at the citrus orchard of Escola Superior de Agricultura de Lavras (ESAL), in Lavras, MG, Brazil, with nine year-old plants on Rangpur lime rootstock. A completly randomized experimental design 2 x 2 factorial scheme with eight replications were used. Plants with or without 90/91production were studied. The thinning of 91/92 production was realized in October. Effects of the past harvest, of fruit thinning of currently crop and its interaction in the off-season production were observed. As lower was the production in the past year provocated by alternate bearing or by thinning, as greater was the off-season production. The major average of season production was 232 fruits per plant.